Pengaruh Media Game Educandy Terhadap Pengetahuan Hipertensi Pada Remaja di Desa Telaga Murni - Zakiya, Rifka Syifa; Kurniasari, Ratih (Jurnal Gizi dan Kuliner, 2021)
Background: knowledge of hypertension in adolescents. Education is one way that can be used to increase one’s knowledge. Educational games are games designed to increase one’s knowledge. Educandy is a web-based game application that can be used as a medium for learning. The educational games used are multiple choice. Objective: The study was conducted to determine the effect of using game media on knowledge of Hypertension in Adolescents. Methods: pre-experimental design research with one group pretest-posttest design. The number of samples was determined by purposive sampling as many as 18 teenagers aged 18-24 years in Telaga Murni Village. Results: the results of this study indicate that there is an increase in knowledge from 12.78 to 14.28. Based on statistical tests using the Wilcoxon test, it was proven that there was an increase in the average score of knowledge before and after being given nutrition education with the "multiple choice" educandy game. This increase in knowledge is caused by the method used, namely nutrition education with educandy games. Conclusion: The use of game media in education has a good effect on increasing knowledge in adolescents. The use of unique and interesting game media will make someone comfortable in using it so that knowledge will be conveyed properly. The weakness of game media requires good internet to access it and its effectiveness is not guaranteed if it is used for areas that have difficult internet access. Key Words: game, hypertension, adolescence